Mode-hop-free wavelength-tunable semiconductor lasers covering the S+C+L band via external-cavity optical feedback - Sheng, Liwen; Liu, Zhiming; Wang, Jianjun; Liu, Lei; Yin, Bingqi; Zhang, Zhihui; Zhou, Shuai; Huang, Lin (Frontiers in Physics, 2025)
A wide mode-hop-free and narrow-linewidth tunable laser diode source employing a Littman-Metcalf configuration with a diffraction grating is developed. We conducted a series of experiments to evaluate the tuning characteristics and spectral linewidth of the proposed external-cavity diode laser. A continuous, mode-hop-free wavelength tuning range of approximately 180 nm within the S+C+L band is achieved, with a spectral linewidth below 32.95 kHz. Moreover, the device maintains an optical signal-to-noise ratio exceeding 62.60 dB and an output power above 10.11 dBm over the entire tuning range under long-term free-running conditions. This tunable laser, offering both mode-hop-free operation and narrow-linewidth output, holds significant promise for practical applications such as coherent detection.